Permutation entropies of short‐term interest rates as an early‐warning signal. (4th June 2019) - Lee, Daeyup; Park, Hail
Abstract: This paper proposes a new method for detecting abnormal movements of short‐term interest rates by using permutation entropy (PE) as a complementary early‐warning signal. Empirical results have shown that the PEs of the US T‐Bill rates plunged below the thresholds of normal movements before the ﬁnancial crisis of 2007–2009, and the PE of 3‐month Euribor similarly dropped before the European sovereign debt crisis of 2010. Additionally, it was found that the PEs of spreads of both domestic interest rates and Libors dropped against the US T‐Bill rates below the thresholds in 2005. This evidence could serve as useful information for policymakers in crisis periods.